A revolução em assuntos militares no contexto da Guerra de Secessão Americana (1861-1865) - Gonçalves, Leandro José Clemente [UNESP] (2015)
Studies made by the defenders of the Arms Raiado Revolution, Military Revolution and the Revolution in Military Affairs, arising at different times of the twentieth century, conceived the idea that technology would be a key factor in the rapid transformation of the war. We believe, however, that although the war becomes she does not accelerated way, but slowly and gradually, in an evolutionary process, and that this transformation is independent of technology. The American Civil War, addressed here as a case study, can reveal, through primary sources, many of the supporters of those three revolution of ideas were wrong in their hasty assessment of this conflict, for men and women who fought in the Civil War did so much that reminds us the tactics of seventeenth and eighteenth centuries than a possible new form of warfare, the modern warfare of the industrial age